Taxonomic revisions of some Neotropical Zygoptera (Odonata) - Garrison, Rosser; Ellenrieder, Natalia Von (Zootaxa, 2024)
We provide updated synonymies for various genera and species of Neotropical Zygoptera based on examination of specimens and literature accompanied by justifications and supported by illustrations. The following generic synonyms are proposed: Austrotepuibasis Machado & Lencioni, 2011 and Pseudotepuibasis Stand-Pérez & Pérez-Gutiérrez, 2020 are junior synonyms of Tepuibasis De Marmels, 2007; Fredyagrion Lencioni, 2022, Kiautagrion Lencioni, 2022, Nathaliagrion Lencioni, 2022, and Machadagrion Lencioni, 2022 are junior synonyms of Leptagrion Selys, 1876; Juenagrion Lencioni, 2023 is a junior synonym of Telebasis Selys, 1865. The following specific synonyms are proposed: Lestes fernandoi Costa, Souza & Muzón, 2006 is a junior synonym of Lestes debellardi De Marmels, 1992; Lestes tikalus Kormondy, 1959 is a junior synonym of Lestes scalaris Gundlach, 1888; Palaemnema brasiliensis Machado, 2009 is a junior synonym of Palaemnema brevignoni Machet, 1990; Hetaerina aurora Ris, 1918 is a junior synonym of Hetaerina duplex Selys, 1853; Hetaerina hebe Selys, 1853 is a junior synonym of Hetaerina longipes Hagen in Selys, 1853; Mnesarete mariana Machado, 1996 is a junior synonym of Mnesarete guttifera (Selys, 1873); Acanthagrion hartei Muzón & Lozano, 2005 is a junior synonym of Acanthagrion obsoletum (Förster, 1914); Oxyagrion bruchi Navás, 1924 is a junior synonym of Oxyagrion ablutum (Calvert, 1909); Austrotepuibasis alvarengai Machado & Lencioni, 2011 and Austrotepuibasis manolisi Machado & Lencioni, 2011 are junior synonyms of Tepuibasis demarmelsi (Machado & Lencioni, 2011). Helveciagrion Machado, 1980 is again considered a junior synonym of Telebasis Selys, 1865; Leptagrion auriceps St. Quentin, 1960 is again considered a junior synonym of Leptagrion macrurum (Burmeister, 1839), and Homeoura sobrina (Schmidt, 1943) is transferred back to Ischnura Charpentier. The following synonymies are tentatively proposed pending further examination of specimens: Philogenia lankesteri Calvert, 1924 is a possible junior synonym of Philogenia carrillica Calvert, 1907; Leptagrion jeromei Lencioni, Vilela & Furieri in Vilela, Garcia Júnior, Furieri & Lencioni, 2021 is a possible junior synonym of Leptagrion andromache Hagen in Selys, 1876; Phoenicagrion flavescens Machado, 2010 is a possible junior synonym of Phoenicagrion flammeum (Selys, 1876); Tuberculobasis mammilaris (Calvert, 1909) is a possible junior synonym of Tuberculobasis croceum (Burmeister, 1839) new combination. The status of Agrion rufovittatum Blanchard, 1846 is briefly discussed.